Preparation and Application of Porous Materials based on Deep Eutectic Solvents. (2nd January 2018) - Li, Xiaoxia; Choi, Jinsub; Ahn, Wha-Seung; Row, Kyung Ho
ABSTRACT: Deep eutectic solvents (DESs) are a common successor to ionic liquids (ILs) with similar physicochemical properties. DESs have attracted considerable interest in related chemical research based on the superiority of DESs over ILs and in the preparation of porous materials. In addition, DESs-based materials have been applied widely in chemical research. This review highlights the preparation and properties of DESs. The application of DES in the preparation of silica and polymers is also discussed. The available data and references in this field are reviewed to summarize the applications and developments of DESs. Based on the development of DESs, the exploitation of new DES-based materials is expected to diversify into chemical research.